2024
DOI: 10.3390/ijms25084504
|View full text |Cite
|
Sign up to set email alerts
|

Periodontitis: A Plausible Modifiable Risk Factor for Neurodegenerative Diseases? A Comprehensive Review

Adelina Plachokova,
Jolijn Gjaltema,
Eliza Hagens
et al.

Abstract: The aim of this comprehensive review is to summarize recent literature on associations between periodontitis and neurodegenerative diseases, explore the bidirectionality and provide insights into the plausible pathogenesis. For this purpose, systematic reviews and meta-analyses from PubMed, Medline and EMBASE were considered. Out of 33 retrieved papers, 6 articles complying with the inclusion criteria were selected and discussed. Additional relevant papers for bidirectionality and pathogenesis were included. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…The results of an observational cohort study indicated that periodontitis is associated with an increase in cognitive decline in Alzheimer’s disease [ 120 ]. The relationship between periodontitis and Alzheimer’s disease is bidirectional [ 121 ]. Therefore, one effective way to prevent AD is to maintain a good diet and good oral hygiene.…”
Section: Factors Influencing the Hyperphosphorylation Of Tau Proteinmentioning
confidence: 99%
“…The results of an observational cohort study indicated that periodontitis is associated with an increase in cognitive decline in Alzheimer’s disease [ 120 ]. The relationship between periodontitis and Alzheimer’s disease is bidirectional [ 121 ]. Therefore, one effective way to prevent AD is to maintain a good diet and good oral hygiene.…”
Section: Factors Influencing the Hyperphosphorylation Of Tau Proteinmentioning
confidence: 99%